Sweeping it under the rug: Positioning and managing pollution‐intensive activities in organizational hierarchies - Lee, Juyoung; Bansal, Pratima (Strategic management journal, 2024)
Research SummaryMany corporate groups have multiple layers with parent companies owning subsidiaries, which own other subsidiaries, and so forth, in a pyramid‐like ownership structure. We argue that corporate groups perform their pollution‐intensive activities at the lower levels of the corporate hierarchy to buffer the parent from pollution‐related regulatory risks. Our analysis of 7400 US‐based business establishments owned by the 67 largest US‐headquartered chemical manufacturing corporate groups supported this argument. We also found that they were even more likely to do so in states with greater environmental stringency, whether it be in the home state of the parent or the host state of the subsidiary. Our research calls into question the effectiveness of environmental regulations if companies have the opportunity to shift polluting activities lower in their corporate hierarchy.Managerial SummaryMany commentators assert that firms offshore or outsource pollution‐intensive activities to avoid environmental regulations. In this research, we suggest a third approach in avoiding environmental regulations: locating pollution lower in the hierarchy of multilayered corporate groups, which are companies that own subsidiaries that own other subsidiaries and so on. By analyzing data on the 67 largest US‐headquartered chemical manufacturing corporate groups, we found support for this assertion. We also found that pollution is more likely to be located lower in multilayered corporate groups when they are subject to stringent environmental regulations. The multilayered corporate form allows parent companies to insulate themselves from the regulatory risks of pollution‐intensive activities of their subsidiaries through their limited liability status.